Kebijakan Penyelenggaraan Perumahan Masyarakat Berpenghasilan Rendah di Kabupaten Lahat Provinsi Sumatera Selatan - Mendra Wijaya; Handrisal Handrisal (Kemudi, 2021)
In essence, the implementing regulations for the construction of housing and settlement areas are clear as the responsibility of the government, as has been described above that the government's role is to determine development in the field of housing and settlement areas. The central government program with 1 (one) million subsidized houses would also pay more attention to its implementation performance, so that the existing implementing regulations will not only become passive laws. In Indonesia today there are still many regulations which in the end become a symptom of problems in their own country. In the context of accelerating housing development for low-income people (MBR), the government makes simplification efforts in simplifying licensing for low-income housing development. By issuing Government Regulation Number 64 of 2016 concerning Low-Income Community Housing Development, then to accelerate its implementation in the regions, it is regulated in Minister of Home Affairs Regulation Number 55 of 2017 concerning the Implementation of Licensing and Non-Licensing of Housing Development for Low-Income Communities (MBR) in the Region. This study aims to determine government policies related to the implementation of MBR housing development and to determine the implementation of Housing Development Permits for Low-Income Communities (MBR) in the Regions, especially in Lahat Regency, South Sumatra Province.